DEVELOPMENT OF THE PHILOLOGY OF THE UZBEK LANGUAGE THE IMPORTANCE OF INFORMATION SOURCES (American Journal of Interdisciplinary Research and Development, 2022)
In World linguistics, in the 20th century, the study of the dichotomy of language and speech, the grammatical possibilities of language in the linguistic system reached a new level. One of the urgent problems is the study of the fact that language is a complex whole in the integrity of speech and speech, that language is realized on the basis of the norm in speech, that it serves as the basis for speech, based on modern scientific and theoretical views and techniques. Today, the study of the grammatical meaning in the integrity of linguistic and pragmatic factors is considered one of the important factors in ensuring the development of such modern areas of linguistics as the rapidly developing pragma linguistics, lingua cultural, ethnolinguistic and psycholinguistic. In World linguistics, great achievements have been achieved in the study of language as a system. In this article, opinions and opinions are made about the importance of information sources in the development of the Philology of the Uzbek language.